Osteopathic support in pregnancy-associated varicose veins: a gentle and holistic approach - Веснін, Володимир Вікторович; Веснін, Максим Вікторович (My University, 2025)
Pregnancy is a physiological state characterized by numerous hemodynamic and hormonal changes, which often contribute to the development or exacerbation of varicose veins. While conventional management includes compression therapy and lifestyle modifications, the role of osteopathy remains underexplored. This study investigates the potential of osteopathic manipulative treatment (OMT) in alleviating symptoms and improving venous return in pregnant women with varicosity.
Keywords: pregnancy-induced varicose; pregnancy; osteopathic techniques; 2025а